Modulations of identities: a regional facade design resource from the aristocratic vernacular - Jahn Kassim, Puteri Shireen; Abdul Majid, Noor Hanita; Mohd Nawawi, Norwina; Raja Abdul Kadir, Tengku Anis Qarihah (2019)
The paper discusses and describes a range of templates, models and variations of tropicalised modulation of facades and recesses from in the local vernacular which convey an aesthetic sense of the region, to counter the homogeneity of modern facades. These range of identified Malay-Nusantara are abstracted from elevations of mansions and palaces which convey a sense of the Classical and which were identified as a new identified substyleof the vernacular. Operationally categorised as a form of Classical vernacular, they represent a rich range of models and templates arising from the region’s past ingenuities that can also transcend the present approach of merely adorining modern structures with Nusantara roofs into a more critical approach. The paper argues that these variations can constitue an untapped resources for creating the modulations of facades in any Nusantara-themes city of the future; without reverting to cosmetic application of motifs and cut-and -paste from the vernacular This language includes key attributes such as proportioned and regular spaces of columns, recesses, projections, staircases and balustrades which are fused in various ways to present a more critical trope of local identity that can be combined and permutate into a tropical ‘facadism’ with a differentiated and dirinctive identity for the south east Asia city in general and the Malay nusantara in particular.